A Buddhist Approach to International Relations Radical Interdependence - Long, William J. (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This book is an open access book. Many scholars have wondered if a non-Western theory of international politics founded on different premises, be it from Asia or from the "Global South," could release international relations from the grip of a Western, "Westphalian" model. This book argues that a Buddhist approach to international relations could provide a genuine alternative. Because of its distinctive philosophical positions and its unique understanding of reality, human nature and political behavior, a Buddhist theory of IR offers a way out of this dilemma, a means for transcending the Westphalian predicament. The author explains this Buddhist IR model, beginning with its philosophical foundations up through its ideas about politics, economics and statecraft. William J. Long is Professor of Political Science at Georgia State University.